If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -4y)(5x + 4y) = 0 Multiply (5x + -4y) * (5x + 4y) (5x * (5x + 4y) + -4y * (5x + 4y)) = 0 ((5x * 5x + 4y * 5x) + -4y * (5x + 4y)) = 0 Reorder the terms: ((20xy + 25x2) + -4y * (5x + 4y)) = 0 ((20xy + 25x2) + -4y * (5x + 4y)) = 0 (20xy + 25x2 + (5x * -4y + 4y * -4y)) = 0 (20xy + 25x2 + (-20xy + -16y2)) = 0 Reorder the terms: (20xy + -20xy + 25x2 + -16y2) = 0 Combine like terms: 20xy + -20xy = 0 (0 + 25x2 + -16y2) = 0 (25x2 + -16y2) = 0 Solving 25x2 + -16y2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16y2' to each side of the equation. 25x2 + -16y2 + 16y2 = 0 + 16y2 Combine like terms: -16y2 + 16y2 = 0 25x2 + 0 = 0 + 16y2 25x2 = 0 + 16y2 Remove the zero: 25x2 = 16y2 Divide each side by '25'. x2 = 0.64y2 Simplifying x2 = 0.64y2 Take the square root of each side: x = {-0.8y, 0.8y}
| 8x+3(0.3)=1 | | 2/3+x=3 | | 3a^2+4a-18=0 | | v+(v-30.8)+(v+23.2)=189.8 | | X-10/3+2x/5+x+10=180 | | 7(1-3y)-2y=-1 | | X-10/3+2x/5+x+10 | | 12=2(4a+2) | | 6y+3=x*x+14x+48 | | (15-2s)(15-2s)=0 | | -4x-7+8=6x+2+8 | | -8(-b)=-6 | | 3x+4(-2)=2 | | 3/3x+5/4x=27 | | -8-6=-6 | | -3x-6=5x-2 | | 16/x=9.32 | | 0.2(0.1x+0.7)=-0.2 | | 2-4y+3y=4 | | 4/5(x)-2+(1/10)x=7 | | C^2-50+23c=0 | | 15/x=9.32 | | 7x-12x=33x+10+2 | | 27x^4+15x^2= | | 4y-1+y+45=8y+50-5y | | 14+4(x-5)=2(3-x) | | 8(8)=48+2x | | 6p^2+12p-94=0 | | (x/3)-2=7 | | -100x^2+400=0 | | 3(4-3y)+4y=2 | | 8+(x/5)=-2 |